(untitled) (Lex localis - Journal of Local Self-Government, 2025)
COVID-19 pandemic caused a drastic increase in medical waste, creating urgent challenges for health and environmental governance. This study aims to analyze how cross-sectoral collaboration was implemented in managing medical waste during the crisis in Kupang City, East Nusa Tenggara Indonesia. Using a qualitative exploratory design, data were collected through interviews, observations, and document reviews, Focus Group Discussion (FGD), then analyzed with coding and NVivo 12 Plus. Findings reveal that organizational involvement was mainly driven by legal mandates, institutional interests, and fear of contamination. Shared motivation was built through trust, mutual understanding, and legitimacy, while capacity for joint action relied on formal procedures (MoU, SOP), informal coordination, and knowledge sharing. Despite barriers such as sectoral ego, limited resources, and fragmented SOPs, collaboration enabled adaptive and coordinated responses. The study proposes a governance model emphasizing leadership, motivation, and organizational capacity as key factors for strengthening future crisis management.